Confucius and the world he created - Schuman, Michael (New York Basic Books, 2015)
Schuman, a Hong Kong-based correspondent for Time, traces the lasting influence of Confucianism in China, despite enormous political and social changes in Chinese society.
How Confucius changed the world -- Confucius becomes Confucius -- Confucius the man -- Confucius the sage -- Confucius the king -- Confucius the oppressor -- Confucius at home, but not at ease -- Confucius the father -- Confucius the teacher -- Confucius the misogynist -- The comeback of Confucius -- Confucius the businessman -- Confucius the politician -- Confucius the Communist -- Seeking the real Confucius.
Includes bibliographical references and index.
Keywords: Confucius